SAR of novel benzothiazoles targeting an allosteric pocket of DENV and ZIKV NS2B/NS3 proteases. (1st October 2021) - Maus, Hannah; Barthels, Fabian; Hammerschmidt, Stefan Josef; Kopp, Katja; Millies, Benedikt; Gellert, Andrea; Ruggieri, Alessia; Schirmeister, Tanja
Graphical abstract: Abstract: In recent years, dengue virus (DENV) and Zika virus (ZIKV), both mosquito-borne members of the Flaviviridae family, have emerged as intercontinental health issues since their vectors have spread from their tropical origins to temperate climate zones due to climate change and increasing globalization. DENV and ZIKV are positive-sense, single-stranded RNA viruses, whose genomes consist of three structural (capsid, membrane precursor, envelope) and seven non-structural (NS) proteins, all of which are initially expressed as a single precursor polyprotein. For virus maturation, the polyprotein processing is accomplished by host proteases and the viral NS2B/NS3 protease complex, whose inhibitors have been shown to be effective antiviral agents with loss of viral pathogenicity. In this work, we elucidate new structure–activity relationships of benzo[ d ]thiazole-based allosteric NS2B/NS3 inhibitors. We developed a new series of Y–shaped inhibitors, which, with its larger hydrophobic contact surface, should bind to previously unaddressed regions of the allosteric NS2B/NS3 binding pocket. By scaffold-hopping, we varied the benzo[ d ]thiazole core and identified benzofuran as a new lead scaffold shifting the selectivity of initially ZIKV-targeting inhibitors to higher activities towards the DENV protease. In addition, we were able to increase the ligand efficiency from 0.27 to 0.41 by subsequent inhibitor truncation and identified N -(5, 6-dihydroxybenzo[ d ]thiazol-2-yl)-4-iodobenzamide as a novel sub-micromolar NS2B/NS3 inhibitor. Utilizing cell-based assays, we could prove the antiviral activity in cellulo . Overall, we report new series of sub-micromolar allosteric DENV and ZIKV inhibitors with good efficacy profile in terms of cytotoxicity and protease inhibition selectivity.